A national overview of paediatric and adolescent and young adult surgical neuro-oncology in Pakistan - Faiza Urooj; Mohammad Hamza Bajwa; Muhammad Usman Khalid; Mashal Murad Shah; Ahsan Ali Khan; Ummey Hani; Altaf Ali Laghari; Jaleed Ahmed Gilani; Noyan Jawed; Muhammad Faraz Raghib; Saad bin Anis; Naveed Zaman Akhunzada; et al. (Journal of the Pakistan Medical Association, 2022)
Objective: To build a comprehensive brain tumour database that will allow us to analyse in detail the prevalence, demographics, and outcomes of the disease in paediatric, adolescent, and young adult age groups. Method: A national cross-sectional study was conducted at 32 centres, and data regarding patient demographics and brain tumours were collected. This data was then stratified based on age groups, healthcare sectors, socioeconomic status, tumour types, and surgical outcomes. Result: Most of the patients who were diagnosed with brain tumours belonged to a lower socioeconomic background and went to public sector hospitals. More males were diagnosed with and treated for brain tumours in the paediatric, adolescent, and young adult populations. The most common tumour in the paediatric population was medulloblastoma (23.7%) and the most common tumour in the adolescent (27.8%) and young adult population (34.7%) was glioma. Significant improvement in KPS scores were seen for: craniopharyngioma (p = 0.001), meningioma (p < 0.0005) and pituitary adenoma (p < 0.0005) Conclusion: This study shows that in all three age groups, there was a greater prevalence in males. Most of the patients belonged to a lower-middle-income class background and most patients presented to public sector hospitals. Greater knowledge of these parameters unique to each age group is the key to understanding and alleviating the burden of disease. Cancer registries, specifically brain tumour registries that keep up-to-date records of these patients, are essential to identify and keep track of these unique parameters to advance medical research and treatment strategies, ultimately lowering the disease burden. Keywords: Pediatric, Neuro-oncology, Adolescent and young adult, AYA, Medulloblastoma, Craniopharyngioma, Epidemiology.